Association of autoimmune diseases with celiac disease and its risk factors - Kayar, Yusuf (Pak J Med Sci, 2019)
OBJECTIVES: Autoimmune Diseases (AIDs) are detected in celiac patients. Our purpose was to determine the AIDs that are associated with celiac disease and related risk factors in the Turkish population. METHODS: The study included 230 celiac patients who were diagnosed and followed-up in our clinics between 2015-2019. All AIDs that accompanied the celiac disease were recorded, and their association with risk factors was analyzed. RESULTS: The mean age of the patients was 35.6±10.6 years (age range:18-72). A total of 58(25.2%) patients were male and the mean age at onset of disease was 29.1±6.5 years. The duration of disease follow-up was 6.5±4.6 years. One hundred and twenty two (53%) patients were on a strict diet, and 72(31.3%) patients had accompanying AID. Hashimoto thyroiditis was found in 39(17%) patients, asthma in 16(7%) patients as the most common comorbidities. There was a significant relation between AID and female gender, age of diagnosis being <40 years, duration of disease, non-GIS symptoms at the time of admission, and non-employment status. CONCLUSION: Screening other AIDs in celiac patients are important, especially in individuals who have risk factors. Considering that many AIDs may develop in the future despite dietary compliance, patients should be followed with a multidisciplinary approach.